Estimating Pore-Size Distributions of Moderately Hydrophobic Mesoporous Solids - Kamil Gierszal; Michal Kruk; Mietek Jaroniec (Adsorption Science & Technology)
In this paper, standard reduced data for adsorption of nitrogen on moderately hydrophobic surface are reported. This surface was obtained by chemical modification of macroporous silica with 3-mercaptopropyltrimethoxysilane. In addition, the statistical film thickness, t curve, is derived using these data and nitrogen adsorption isotherms measured on two large-pore ordered mesoporous silica MCM-41 samples modified with the same organosilane. The application of these reference adsorption data is shown in the evaluation of pore-size distribution and in the related characterization of mesoporous materials with moderate surface hydrophobicity.